Constrictive Pericarditis in a Hemodialysis Patient Who Presented with Rapidly Progressive Pericardial Calcification: A Diagnostic Challenge – A Case Report - Oho Tsunematsu; Shin-ichi Takeda; Mitsutaka Yamaguchi; Miwa Kaneko; Kazuho Oe; Yoshiaki Murakami; Daisuke Nagata (Case Reports in Nephrology and Dialysis)
Introduction: Constrictive pericarditis (CP) is characterized by impaired diastolic filling of the ventricles, which typically causes right heart failure. Its diagnosis may be challenging because it mimics other disorders. Furthermore, prompt diagnosis and treatment are more crucial in cases of hemodialysis; otherwise, maintenance dialysis would be hampered by severe hypotension. Case Presentation: We report the case of a 53-year-old man on hemodialysis who developed CP with shock. His blood pressure was 55/30 mm Hg at the time of hospitalization due to presyncope. He continued hemodialysis but with some difficulty. However, right pleural effusion persisted because of impaired fluid removal by hemodialysis. Despite such severe manifestations, the distinctive clinical features of CP were lacking. By carefully evaluating the time course of computed tomography images, progressive calcification in the pericardium emerged as a significant clue. Cardiac catheterization subsequently revealed a dip-and-plateau pattern of right ventricular pressure, which led to a definitive diagnosis of CP. Soon after the diagnosis, he underwent successful surgery. Conclusion: An important finding was that, unlike calcific lesions in the general dialysis population, the patient’s calcific lesions were mostly confined to the pericardium and progressed on a monthly basis. Thus, the present case may provide deep insight into the diagnosis of CP and the management of hemodialysis patients with severe hypotension.